ACTION RESEARCH THROUGH THINK TALK WRITE TECHNIQUE (T2WT) IN WRITING NARRATIVE TEXT FOR JUNIOR HIGH SCHOOL STUDENTS AT SMP BUDI MURNI 1 MEDAN - Saida Sara Simatupang; Azizah Husda; Fitriany Fitriany; Michele Sesilia Samosir; Cecilia Evelyn Siregar (Jurnal Basataka (JBT), 2024)
Writing skill is one of the basic competencies in English learning, but many students have difficulty in developing this skill, including in writing narrative text. This study aims to improve the narrative writing skills of grade VIII students at SMP Budi Murni 1 Medan through the application of Think-Talk-Write (T2W) technique. Writing skill is a basic competency in English learning, but many students have difficulties, especially in writing narrative texts. The subjects of this study were 27 students at SMP Budi Murni 1 Medan, using the Kemmis and McTaggart model of Classroom Action Research (PTK) method consisting of two cycles. The results showed that 60% of the students achieved the Very Good category and 40% achieved the Good category in cycle II, with all groups successfully meeting the minimum passing score of 70. This improvement was due to the implementation of group discussion in the “Talk” stage, which helped students organize ideas more structurally before writing, as well as clarity of instructions and better time management in Cycle II. Thus, this study concludes that the Think-Talk-Write (T2W) technique is effective in improving junior high school students' narrative writing skills and is recommended to be applied in English language learning.